Status of the Ganges river shark Glyphis gangeticus (Müller & Henle, 1839) (Dhaka University Journal of Biological Sciences, 2017)
Abstract not availableDhaka Univ. J. Biol. Sci. 26(1): 111-116, 2017 (January)